Expressive Speech Acts Analysis of Jesse In El Camino: A Breaking Bad Movie 2019 - Acmad Zafir Al Chairi; Ririn Setyowati (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
This study aims to find how the types and functions of expressive speech acts contained in Jesse's speech in the film El Camino: A Breaking Bad Movie affect Jesse's utterances in the film. This research used the descriptive qualitative method because the data came from utterances in the form of characters' conversational words in the film. Based on the analysis, the researcher identified six types of expressive speech acts out of nine examined. These types include thanking, apologizing, deploring, complimenting, complaining, and welcoming. Additionally, the researcher discovered eight functions of expressive speech acts from the ten examined. These functions are showing gratitude, appreciation, regret, heartfelt emotion, praise, empathy, dissatisfaction, and acceptance. In this study, each type of expressive speech act is connected to a specific function, emphasizing the importance of that function in expressing the speaker's intention. Therefore, some data in this study may reflect more than one function, as the speaker intends to convey a message that serves multiple purposes, as each utterance can carry meanings beyond their literal interpretation. The results of the analysis show that the expressive utterances used by the character affect the character's actions towards the situation and affect the meaning of the character purposes.